Jadîr al-Wasâ’il iSpring Suite bi Android fi Talim al-Qawâ’id al-Lughah al-‘Arabiyyah - Wakhidatus Syifa'; Siti Sulaikho; Khoirun Nisa Al Wachidah (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2021)
Purpose-This study aimed at analizing the effectiveness of android-based iSpring Suite learning media to improve student learning achievement of Nahwu dan Shorof. Design/Metodology/Approach-The study used research and development research design with 4D Thiagarajan. Quantitative apporach and statistic descriptive was also used in this study. The sample involves 35 eighth grade students from three classes in MTs. Al Hikmah Jombang. The research instrument for interview guideline, observation sheet, questionnaires for revealing the students’ need of iSpring Suite learning media, and media expert validation questionnairs which covered subject master expert and subject master linguist. The results show that the iSpring Suite learning media was able to facilitate teachers in developing learning models. Findings-The iSpring Suite learning media with android based for Nahwu and Shorof became an interactive medium to improve student achievement. The quizzes on android-based iSpring Suite interactive learning media on Nahwu and Shorof were in the form of multiple choice and true/false. The results of the student scores appeared in the teachers e-mail. The 35 samples involved expressed their interest in using the android-based iSpring Suite learning media in Nahwu and Shorof subjects. Research Limitation/implications- The research cannot go deeper into dialogue simulation in the iSpring Suite because the development foccused only on learning materials, videos and quizzes. However, the research found out that the iSpring Suite learning media successfully assisted teachers to develop a learning media to improve the student achievement. Keywords: learning media, iSpring Suite, android-based, Nahwu, Shorof